Pemberdayaan Kelompok Tani Perempuan Sion Melalui Vertikultur dan Penerapan Integrasi Ternak-Tanaman Budidaya Pakcoy di Pekarangan - Wilda Lumban Tobing; Boanerges Putra Sipayung; Achmad Subchiandi Maulana; Kristoforus Wilson Kia; Adolfianus Nino; Primus Ena Kaet; Maria Apriana Manehat; Elviani Seran; Marianus Asa; Carolus Emerik Kato (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
The purpose of this community service is to increase the knowledge and skills of farmer groups in applying the concept of livestock-plant integration and verticulture to Pakcoy cultivation in yard lands. The methods used in this service are counseling and demonstration methods. This community service activities are carried out in the yard lands of the Sion Women's Farmer Group in Sasi Village, Kota Kefamenanu District, North Central Timor Regency. The activity involved a farmer group consisting of 6 (six) people, servants, students and the surrounding community who accidentally saw the activity. Based on the community service activities, it was found that the Sion Women Farmer Group was able to (1) use a verticulture system with the concept of livestock-plant integration in Pakcoy cultivation in yard lands, (2) utilize chicken livestock waste into bokashi as a composition for planting media for Pakcoy cultivation, (3) utilize yards as more productive agricultural land, (4) meet the food needs of the family, and (5) manage time and labor.